In vivo characterization of carbon dots–bone interactions: toward the development of bone-specific nanocarriers for drug delivery. (1st January 2021) - DuMez, Rachel; Miyanji, Esmail H.; Corado-Santiago, Lesly; Barrameda, Bryle; Zhou, Yiqun; Hettiarachchi, Sajini D.; Leblanc, Roger M.; Skromne, Isaac
Abstract: Current treatments for osteoporosis and other bone degenerative diseases predominately rely on preventing further bone erosion rather than restoring bone mass, as the latter treatments can unintentionally trigger cancer development by undiscriminatingly promoting cell proliferation. One approach to circumvent this problem is through the development of novel chemical carriers to deliver drug agents specifically to bones. We have recently shown that carbon nanodots (C-dots) synthesized from carbon nanopowder can bind with high affinity and specificity to developing bones in the larval zebrafish. Larval bones, however, are physiologically different from adult bones in their growth, repair, and regeneration properties. Here we report that C-dots can bind to adult zebrafish bones and that this binding is highly specific to areas of appositional growth. C-dots deposition occurred within 30 minutes after delivery and was highly selective, with bones undergoing regeneration and repair showing higher levels of C-dots deposition than bones undergoing normal homeostatic turnover. Importantly, C-dots deposition did not interfere with bone regeneration or the animal's health. Together, our results establish C-dots as a potential novel vehicle for the targeted delivery of drugs to treat adult bone disease.